The cases of successful endoscopic removal of Type A and Type B stent-stone complex each by peroral cholangioscopy-directed lithotripsy - Fujita, Yasuaki; Okumura, Fumihiro; Kito, Yusuke; Haneda, Kenichi; Suzuki, Yuta (Tando, 2021)
Case1: A 82-year-old man had undergone endoscopic stenting for biliary stenosis caused by autoimmune pancreatitis. At follow-up 51 months after stent placement, Type A stent-stone complex (SSC) was formed around the plastic stent. Since endoscopic choledocholithiasis lithotripsy failed due to impacted stone, we removed the SSC by peroral cholangioscopy-directed lithotripsy (POCSL).Case2: A 87-year-old man had undergone endoscopic stenting for distal bile duct benign stenosis. At follow-up 23 months after stent placement, the Type B stent-stone complex (SSC) was formed into the inward migrated metalic stent. Since the SSC was large and impacted to the bile duct, we crushed the SSC by POCSL and removed the metallic stent.SSC is one of the complications related long term bilialy stent placement, but there are still few reports of SSC. We report two cases, one for each of Type A and Type B SSC, treated by POCSL successfully.